New records of myxomycetes from Russia and Mongolia and phylogeny of Perichaena brevifila - Vlasenko, Anastasia V.; Dejidmaa, Turmunkh; Zibzeev, Evgeny G.; Baturin, Sergei O.; Bondar, Aleksander A.; Chelobanov, Boris P.; Vlasenko, Vyacheslav A. (Phytotaxa, 2025)
New records are presented for eight species of myxomycetes, including three for Russia and four for Mongolia. Of these, Calonema dissipatum, Perichaena brevifila and Trichia heteroelaterum are very rare on a global scale. Arcyria afroalpina is the first record in Russia and mainland Asia; Calonema dissipatum is the second record in the world, the first record in Russia and in Northern Asia; Perichaena brevifila is the second record in Russia and Asia; Trichia heteroelaterum is the third record in the world, and first record in Russia and in Northern Asia. Cribraria macrocarpa, C. mirabilis, C. purpurea, Metatrichia asiatica and Physarum aeneum are the first records in Mongolia. The 18S nrDNA sequence for Perichaena brevifila was obtained for the first time, allowing the phylogeny of the species to be determined. Photographs of fruiting bodies of the identified species in reflected light, microstructures in transmitted light and in SEM are presented.